Tubular Surfaces Around Timelike Biharmonic Curves in Lorentzian Heisenberg Group Heis3 - Korpinar, Talat; Turhan, Essin (Ovidius Univ Press, 2012)
In this paper, we describe a new method for constructing a tubular surface surrounding a timelike biharmonic curve in the Lorentzian Heisenberg group Heis(3). Firstly, we characterize timelike biharmonic curves in terms of their curvature and torsion. Also, by using timelike biharmonic curves, we give explicit parametrizations of tubular surfaces in the Lorentzian Heisenberg group Heis(3).
Keywords: Tubular Surface; Biharmonic Curve; Heisenberg Group